The Case for Agricultural Climate Services in Africa - Hansen, James; Bradley-Cook, Julia; Apotsos, Alex; Blumenstock, Ali; Vaughan, Catherine; Carr, Edward R. (Climate Links, 2020)
Ninety percent of the world’s farms are managed by small-scale farmers, feeding millions of people. Unfortunately, those farmers face significant impacts from climate variability and change. These impacts disrupt their ability to meet livelihoods and sustenance needs, and to produce enough food for a growing world. Climate services provide information about these impacts and aim to support agricultural decision-making for improved livelihoods, resilience, and food security.